A Rapid Recovery Protocol Applied to Total Joint Arthroplasty Reduced Readmissions for Surgical but Not Medical Reasons Over a 5-Year Period. Issue 2 (July 2021) - Turcotte, Justin; Menon, Nandakumar; Angeles, Jeanne; Zaidi, Amina; King, Paul; MacDonald, James
Background : Total hip arthroplasty (THA) and total knee arthroplasty (TKA) are commonly performed procedures that are expected to continue increasing in demand. Although they are proven to be safe and effective, emergency room (ER) visits or hospital readmissions within 90 days after these procedures account for more than one-third of the total cost of postacute care. Purpose : We sought to identify changes in reasons for 90-day ER visits and readmissions after total joint arthroplasty (TJA) during a 5-year period over which rapid recovery protocols evolved. Methods : We conducted a retrospective cohort study comparing 1980 patients who had undergone TJA from July 2017 to June 2018 with a previously published cohort of 7466 patients who had undergone TJA from July 2013 to June 2017. All procedures were performed at a single institution. Changes in the proportion of patients returning for medical and surgical reasons were compared using univariate analysis. Results : For patients discharged home, the 2017–2018 cohort showed a significant reduction in the proportion of ER visits due to pain and swelling and wound infection and an increase in visits for medical reasons. This cohort had a higher proportion of readmissions for medical reasons. In patients discharged to a skilled nursing facility (SNF), similar reasons for ER visits were observed across time periods, and a decrease in the proportion of readmissions for wound infections was observed in the 2017–2018 cohort. Falls and nausea, vomiting, or diarrhea increased significantly to account for 9.5% of readmissions each in 2017–2018. Conclusion : The results of a comparison of 2 cohorts demonstrate the heterogeneous and dynamic nature of unplanned return-to-hospital events and the importance of patient support throughout the surgical episode. As we strive toward minimizing ER visits and readmissions after TJA, rapid recovery protocols must continue to evolve to address the complexity of this patient population.